Conference between the Federated Engineering Employers and the Joint- Committee of Affiliated Trade Unions held [...] on 24th, 25th, 26th, and 30th November, and 1st, 2nd, 3rd, 14th, 15th, 16th, and 17th December, 1897 (Aird and Coghill])
With index.